Repair of 3-methyladenine and abasic sites by base excision repair mediates glioblastoma resistance to temozolomide - Silber, John R.; Bobola, Michael S.; Kolstoe, Douglas D.; Blank, A; Chamberlain, Marc C. (Frontiers in Oncology, 2012)
Alkylating agents have long played a central role in the adjuvant therapy of glioblastoma multiforme (GBM). More recently, inclusion of temozolomide (TMZ), an orally administered methylating agent with low systemic toxicity, during radiotherapy and afterward has markedly improved survival. Extensive in vitro and in vivo evidence has shown that TMZ-induced O6-methylguanine (O6-meG) mediates GBM cell killing. Moreover, low or absent expression of O6-methylguanine-DNA methyltransferase (MGMT), the sole human repair protein that removes O6-meG from DNA, is frequently associated with longer survival in GBMs treated with TMZ, promoting interest in developing inhibitors of MGMT to counter resistance. However, the clinical efficacy of TMZ is unlikely to be due solely to O6-meG, as the agent produces approximately a dozen additional DNA adducts, including cytotoxic N3-methyladenine (3-meA) and abasic sites. Repair of 3-meA and abasic sites, both of which are produced in greater abundance than O6-meG, is mediated by the base excision repair (BER) pathway, and occurs independently of removal of O6-meG. These observations indicate that BER activities are also potential targets for strategies to potentiate TMZ cytotoxicity. Here we review the evidence that 3-meA and abasic sites mediate killing of GBM cells. We also present in vitro and in vivo evidence that alkyladenine-DNA–glycosylase, the sole repair activity that excises 3-meA from DNA, and Ape1, the major human abasic site endonuclease, mediate TMZ resistance in GBMs and represent potential anti-resistance targets.